Experimental and simulation study on efficient CH4/N2 separation by pressure swing adsorption on silicalite-1 pellets - Yang, Jiangfeng; Bai, Honghao; Shang, Hua; Wang, Jun; Li, Jinping; Deng, Shuguang (Chemical engineering journal (Lausanne, Switzerland : 1996), 2020)
•Silicalite-1 pellets sorbent for PSA separation of CH4 and N2 (20%/80% and 30%/70%).•Unimpaired adsorption and separation performances on silicalite-1 pellet.•20% and 30% CH4 could be enriched to 45% and 57% by a single column with a recovery of 80%.•The two-bed six-step cycles could be accurately simulated. In this work, we have studied high-silica (Si/Al = 200) zeolite silicalite-1 pellets sorbent for the separation of methane and nitrogen in a pressure swing adsorption (PSA) process. The pellet samples have well maintained similar adsorption and separation performances of the zeolite powder samples. The adsorption kinetic parameters were determined by actual breakthrough experiments on the pellet samples. The effects of feed flow and cycle time on methane product purity and recovery have been investigated. The accuracy of the numerical simulation method has been verified by the experiment data. In order to optimize the coalbed methane enrichment performance, the two-bed six-step PSA cycle was applied in the simulation. The simulation results revealed that 45% and 57% methane concentration could be achieved from 20% and 30% methane feedings with a recovery above 80%.